THE ROLE OF PHYSICAL ACTIVITY IN THE TREATMENT OF PATIENTS WITH ARTERIAL HYPERTENSION AND OBESITY - Psarova, Valentyna; Kochuieva, Maryna; Komissarova, Olha; Kyrychenko, Nataliia; Kochuiev, Gennadii; Kushnir, Vasyl; Cherkashyna, Anastasiia (Eastern Ukrainian Medical Journal, 2023)
The study aimed to assess the impact of physical activity on the dynamics of neurohumoral and cardio hemodynamic indicators in patients with arterial hypertension and concomitant obesity under different pharmacotherapy regimens. Materials and Methods: Two hundred patients with stage II arterial hypertension grade 2 and obesity grade I–II were examined using clinical-anamnestic, anthropometric, biochemical, automated immunological analysis, spectrophotometric and instrumental methods. Per the research objective, patients underwent a re-evaluation after six months of prescribed treatment. Non-pharmacological treatment included dietary therapy aimed at weight correction, with recommendations to increase physical activity primarily through brisk or moderately brisk walking for at least 45 minutes daily. Pharmacological treatment followed the European recommendations in 2018, involving dual antihypertensive therapy. The combination included perindopril and amlodipine. Patients who achieved target BP levels within 3 months of treatment continued to receive the prescribed therapy. For the rest of the patients, a third antihypertensive drug, indapamide, was additionally prescribed. In addition to assessing the achievement of target blood pressure levels after 6 months and at interim stages of the study, patients’ adherence to recommendations regarding expanding physical activity was evaluated. Patients were divided into groups with sufficient and reduced physical activity accordingly. Statistical analysis of the obtained data was conducted using the SPSS 17 software package (IBM), Microsoft Office Excel-2003. The data are presented as mean values ± standard deviation. Significance was established at the level of p < 0.05 in all cases. Results of the study: Patients who achieved target blood pressure levels on dual antihypertensive therapy and had sufficient physical activity after six months of treatment differed significantly from patients with low physical activity levels. They exhibited lower values of the pulse wave velocity in the carotid artery and abdominal aorta, a considerably higher degree of endothelium-dependent vasodilation, lower values of end-systolic and end-diastolic diameters, left ventricular mass, a lower E/e´ ratio, and showed better dynamics in metabolic and pro-inflammatory indicators. Additionally, they had a higher level of antioxidant protection. Patients who reached the target blood pressure levels on three-component antihypertensive therapy and engaged in sufficient physical activity after six months displayed significant differences compared to patients with low physical activity. These differences included a more substantial reduction in the pulse wave velocity in the carotid artery, an increase in endothelium-dependent vasodilation, lower indicators of carbohydrate metabolism, reduced levels of pro-inflammatory and pro-oxidant activity, lower levels of leptin, and a more pronounced increase in adiponectin. Conclusions: Physical activity is a crucial factor influencing the treatment outcomes for patients with arterial hypertension and obesity across different antihypertensive therapy regimens. Irrespective of the chosen antihypertensive therapy option, physical activity positively impacted cardiovascular remodelling, the dynamics of metabolic and pro-inflammatory indicators, and the equilibrium within the oxidative stress-antioxidant protection system and activity of the renin-angiotensin-aldosterone system.